Ecclesiastical Curiosities - Andrews, William, 1848-1908 (Salt Lake City, UT : Project Gutenberg, 2011)
"Ecclesiastical Curiosities" by William Andrews is a collection of essays exploring various aspects of ecclesiastical architecture and traditions, likely written in the late 19th century. The work delves into the significant and often overlooked elements related to church design and customs, such as church doors, sacrificial foundations, and the evolution of English cathedrals. Each essay is crafted by different contributors who provide insights into specific topics within the larger theme of ecclesiastical history. The opening of the text introduces a preface by Andrews himself, followed by the first essay titled "The Church Door," credited to the Rev. Geo. S. Tyack. This initial exploration emphasizes the importance of church doorways in shaping visitor expectations of the interior's grandeur. Tyack discusses historical practices surrounding church entrances, detailing their architectural significance and the various cultural customs associated with them throughout different eras, such as the symbolic meanings attached to different types of doors and their decorations. This sets the tone for a deeper dive into the historical and cultural layers that inform modern ecclesiastical architecture, inviting readers to appreciate not only the buildings themselves but also the rituals and beliefs they embody. (This is an automatically generated summary.)
Release date is 2011-12-11
Produced by David Wilson
Keywords: Churches -- England; Christian antiquities -- England